Hlf Expression Marks Early Emergence of Hematopoietic Stem Cell Precursors With Adult Repopulating Potential and Fate - Tang, Wanbo; He, Jian; Huang, Tao; Bai, Zhijie; Wang, Chaojie; Wang, Haizhen; Yang, Ruichuang; Ni, Yanli; Hou, Jun; Wang, Junliang; Zhou, Jie; Yao, Yingpeng; et al. (Frontiers in Cell and Developmental Biology, 2021)
In mouse aorta-gonad-mesonephros (AGM) region, pre-hematopoietic stem cells (pre-HSCs) are generated from rare and specialized hemogenic endothelial cells (HECs) via endothelial-to-hematopoietic transition (EHT), followed by maturing into bona fide hematopoietic stem cells (HSCs). As HECs also generate a lot of hematopoietic progenitors not fated to HSCs, powerful tools that are pre-HSC/HSC-specific become urgently critical. Here using gene knockin strategy, we firstly developed a Hlf-tdTomato reporter mouse model, and detected Hlf-tdTomato expression only in part of the immunophenotypic CD45- and CD45+ pre-HSCs in E10.5 AGM region. By in vitro co-culture together with long-term transplantation assay stringent for HSC precursor identification, we further revealed that unlike the CD45- counterpart in which both Hlf-tdTomato-positive and negative sub-populations harbored HSC competence, the CD45+ E10.5 pre-HSCs existed exclusively in Hlf-tdTomato-positive cells. The result indicates that cells must obtain Hlf expression prior to or together with CD45, otherwise they cannot further proceed into the HSC stage. Furthermore, we constructed a novel Hlf-CrexER mouse model and performed time-restricted genetic lineage tracing by a single dose induction at E9.5. We observed the labeling in E11.5 AGM precursors and their contribution to the immunophenotypic HSCs in fetal liver. Importantly, these Hlf-labeled early cells contributed to and retained the size of the HSC pool in the bone marrow, which continuously differentiated to maintain a balanced and long-term multi-lineage hematopoiesis in the adult. Therefore, we provided another valuable mouse model to specifically trace the fate of emerging HSCs in the mid-gestation embryo.